The effect of customer empowerment and customer engagement on marketing performance: The mediating effect of brand community membership - Anber Abraheem Shlash Mohammad (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
This study aimed at examining the mediating role of brand Community membership on the effect of customer empowerment and customer engagement on marketing performance. The population of the study contained students of universities in the North Region of Jordan. A total of 1320 questionnaires were administered to sample members, and 895 questionnaires were returned completed. Data analysis indicated a significant partial mediation of brand community in the effect of customer empowerment on customer satisfaction but not in the effect of customer engagement and customer loyalty. Interestingly, the results confirmed that employee engagement is more important for organisations to ensure customer loyalty. The effect of customer empowerment on customer satisfaction was mediated by the customer's membership to the brand community. Thereupon, organisations should ensure put their customers' engagement as a priority. Further research is required to investigate the predictability of both customer satisfaction and engagement using different samples from several settings.
Keywords: M31; 650; customer empowerment; customer satisfaction; brand community; customer engagement; customer loyalty